2010
DOI: 10.1177/0269216310376260
|View full text |Cite
|
Sign up to set email alerts
|

The use of morphine to control pain in advanced cancer: an investigation of clinical usage in Bangladesh

Abstract: In 2007, 13% of all deaths worldwide were due to cancer, and of these 72% occurred in low- and middle-income countries. Opioids are essential for the successful delivery of palliative care and pain control. This paper reports data from a cross-sectional survey that aimed to investigate the use of morphine in advanced cancer in palliative care setting in Bangladesh, in order to inform clinical practice and fledgling service development. The study was a single semi-structured qualitative interview study. Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…However, its use may be erratic given that PC is an emerging concept where physicians may lack experience in PC and the use of opioids for patients who are dying and/or for extended periods. In areas where PC is not well developed, several barriers to prescribing morphine have been reported including availability of the drugs, limited knowledge and opiophobia among physicians, along with the in uence of patients and families [54,55]. The high demonstrated need for improved pain control highlight this as a priority area for development in new PC services in the Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use may be erratic given that PC is an emerging concept where physicians may lack experience in PC and the use of opioids for patients who are dying and/or for extended periods. In areas where PC is not well developed, several barriers to prescribing morphine have been reported including availability of the drugs, limited knowledge and opiophobia among physicians, along with the in uence of patients and families [54,55]. The high demonstrated need for improved pain control highlight this as a priority area for development in new PC services in the Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…Addiction: More physicians (89%) displayed concern about the rapid development of tolerance and addiction than physicians in other studies 13 . This concern had reflected significantly in their attitude towards opioid prescribing.…”
mentioning
confidence: 84%
“…A qualitative study reported the barriers of opioids use in Bangladesh as: inadequate dosing, interrupted drug supply, legal restrictions and unavailability of immediate release morphine 13 . Opioid consumption in Bangladesh in 2012 was only 0.05 mg/capita 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To convene the huge challenge in Bangladesh, palliative care needs to be mainstreamed into the accessible healthcare scheme for a possible and sustainable public health advance [2]. In 2007, 13% of all deaths global were owed to cancer and among them 72% took place in low and middle-income countries like Bangladesh [3].…”
Section: Introductionmentioning
confidence: 99%